Enforcing peace agreements through commitment technologies - S. Mansoob Murshed; Philip Verwimp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper models the instability of peace agreements, motivated by the empirical regularity with which peace agreements tend to break down following civil war. When war provides opportunities for profit to one side, or when other difficulties such as historical grievances exist, peace may become incentive incompatible. The party that has something to gain from surprise warfare may agree to peace, but will later renege on it. It is shown that the levels of conflict chosen by this group are an increasing function of both grievance and greed, but decreasing in the direct costs of war. Peace is achievable via externally devised mechanisms that enhance commitment to peace. Aid and direct military peacekeeping intervention (sanctions) can reduce or eliminate conflict. These sanctions, however, need to be credible. Finally, the independent provision and finance of international sanctions are considered. When these arrangements yield little benefit to financial sponsors, or are very costly to them, the bite of the sanctions can become ineffective.
Keywords: C78; D72; D74; D83; 330; commitment problems; peace treaties; commitment technologies; sanctions; Friedenssicherung; Verhandlungstheorie